Effect of intercellular collisions on red blood cell membrane damage - Hristo Valtchanov; Renzo Cecere; Rosaire Mongrain (Scientific Reports)
Abstract Modelling blood flow and particularly cellular damage induced by supra- and non-physiological blood-flow conditions is crucial when developing novel blood-exposed biomedical devices and treatments. Blood is composed of 30–50% red blood cells (RBCs) by volume, yet the mechanisms and effects of intercellular collisions are frequently neglected in red blood cell damage models. These effects are investigated by employing fully coupled 3D fluid structure-interaction simulations to simulate the collision processes in a Couette shear flow and to gauge their effect on the strain experienced by the RBC membrane as well as the transmembrane hemoglobin diffusion rate. Intercellular collisions are found to nearly double the membrane strain at hemolytic shear rates, with declining effect as the shear rate increases, and have a similar effect on sublethal hemoglobin diffusion. Viscoelastic simulations were conducted to examine the effect of incorporating membrane viscosity on the strain experienced by red blood cell membrane during collisions, and find minimal impact of incorporating viscoelasticity at high shear. Incorporating the effect of intercellular collisions is found to be a crucial factor for predicting stress-induced cellular damage under dynamic conditions.